"Nowadays there is gender": "Doing" global gender equality in rural Malawi. (February 2020) - Adolfsson, Johanna Sofia; Madsen, Ole Jacob
This article analyzes the intersection of psychology with global development policy and practice, reviewing how gender as a concept is negotiated and understood amongst men and women in rural Malawi. We argue that gender, considered from a psychological perspective, has been narrowed down to meet the standards of global policy actors. By empowering individuals to "self-actualize, " policy implementers expect social and economic spin-off effects such as lower birth rates, higher education levels, and poverty reduction. The focus on individuals acts to obscure the broader structural power inequities, is especially prevalent in rural Malawi. To explain this, we use Haslam's idea of "concept creep, " on how psychological concepts tend to affect other institutional traditions. The everyday understandings of gendered life described here show how gender is a fluid concept that shifts according to cultural, social, and ideological norms.